Nimbus.: повесть о докторе Гаазе / Александр Нежный. - Нежный А. (Центр книги Рудомино, 2013)
Экземпляры: аб. (20141128) / Инвентарный номер: 1942 / Цена: 220.00 / Авт.знак: Н 43 / ГРНТИ: 17 / ББК: 84(2Рос-Рус)6